2004
DOI: 10.1897/03-90
|View full text |Cite
|
Sign up to set email alerts
|

Uranium complexation and uptake by a green alga in relation to chemical speciation: The importance of the free uranyl ion

Abstract: The bioavailability and toxicity of dissolved metals are closely linked to the metals' chemical speciation in solution. Normally the complexation of a metal by a ligand would be expected to decrease its bioavailability. The aqueous speciation of uranium (U) undergoes tremendous changes in the presence of ligands commonly found in natural waters (carbonate, phosphate, hydroxide, and natural organic matter). In the present project, links between speciation, medium composition, and bioavailability of uranium towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
61
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 39 publications
6
61
0
Order By: Relevance
“…These results also substantiate earlier reports that U biosorption decreases with increasing pH and increasing carbonate/bicarbonate concentration due to the higher degree of complexation of uranyl ion by hydroxides and carbonates (9,18,45). It has also been shown that increasing pH and higher bicarbonate/carbonate concentration exert lower toxicity (46)(47)(48), as in the presence of high carbonate concentration, bioaccumulation of U is reduced in bacteria, consequently leading to increased U tolerance (17,18,49).…”
Section: Discussionsupporting
confidence: 91%
“…These results also substantiate earlier reports that U biosorption decreases with increasing pH and increasing carbonate/bicarbonate concentration due to the higher degree of complexation of uranyl ion by hydroxides and carbonates (9,18,45). It has also been shown that increasing pH and higher bicarbonate/carbonate concentration exert lower toxicity (46)(47)(48), as in the presence of high carbonate concentration, bioaccumulation of U is reduced in bacteria, consequently leading to increased U tolerance (17,18,49).…”
Section: Discussionsupporting
confidence: 91%
“…Unfortunately, many toxicity tests concern organisms at particular life stages and experiment duration may be short relative to total lifespan meaning that our method must be able to extrapolate effects across life stages. An additional complex issue for extrapolation purposes is accounting for the relationship between U speciation and water hardness and pH in combination with toxic effects (Fortin et al, 2004(Fortin et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…isolate (hereafter referred to as isolate A) cultured from the Cold Test Pit South (CTPS) at the INL. Previous studies have concluded that UO 2þ 2 toxicity and bioaccumulation potential is strongly influenced by complexation and speciation of the UO 2þ 2 [22,23], and, therefore, when possible, differences in toxicity and bioaccumulation patterns were associated with changes in UO 2þ 2 speciation.…”
Section: Introductionmentioning
confidence: 99%